Dampak Dampak Digital Marketing Terhadap Kinerja UMKM Di Kota Kupang Pada Masa Pandemi Covid-19 - Yuan Valentino Elim; Mariano Nugraha; Zulkifly Umar; Aprianus Ronny Modena (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The Covid pandemic has had an impact on the declining performance of MSMEs in Kupang City. Various efforts have been made by the government to save MSMEs and one of them is use of digital marketing. This study aims to determine the impact of the use of digital marketing on the performance of SMEs in Kupang City and identify the obstacles faced by SMEs in the use of digital marketing. The results of this study indicate that using digital marketing in marketing products/services to MSMEs in Kupang City is able to have an impact on sales growth, increasing income, expanding market reach and increasing the number of customers. In addition, there are several obstacles faced by MSMEs in using digital marketing, namely lack of understanding of business via the internet, limited financing, unprepared labor, lack of availability of supporting facilities, unstable internet network, and distrust of business in internet